Muslim consumers’ awareness levels on halal vinegar products: a case study in Selangor - Harahap, Iswandi; Muhamad Shukri, Abdul Salam @ Zulkifli; Sulong, Moohamad Ropaning; Md Rahim, Nasrudin; Azman, Sulaiman Abdul Haq (Usuli Faqih Research Centre PLT, 2021)
Vinegar is one of the oldest condiments used to this day. The Muslim community considers vinegar a halal product because the Prophet Muhammad (S.A.W) used it as a condiment. However, the ruling of vinegar is not explicitly mentioned in the al-Quran and al-Hadith and even the al-Quran does not specifically mention vinegar, unlike the khamr in which the rule is qaṭ'ī (clear). The absence of these clear guidelines has led to controversy among consumers, where some users were aware of the halal status of vinegar while others are not concerned about it. In this regard, this research aims to study the awareness and concern of Muslim consumers on halal vinegar products in Selangor, Malaysia. A total of 241 users from nine districts in Gombak, Hulu Langat, Hulu Selangor, Klang, Kuala Langat, Kuala Selangor, Petaling, Sabak Bernam and Sepang were selected as respondents using the random sampling method. The information was collected using questionnaire and Google Doc form which was completed by the respondents. The data obtained were analyzed using Statistical Package for Social Sciences (SPSS). The survey found that almost half of the respondents (46.1%) were aware of the existence of various types of vinegar in the Malaysian market. The majority of respondents were very careful in choosing a halal product especially in vinegar product where 90.9% of the respondents only chose halal Muslim vinegar products. However, only 36.1% of the respondents were aware of the product produced through the process of fermentation such as vinegar containing alcohol and therefore only 34.4% found that vinegar also contained alcohol and the level of consumer awareness of the alcohol limit allowed in food and beverages was just 28% of all respondents. However, the majority of respondents were aware that the percentage of alcohol contained in the product will affect the halal status of the product. 53.9% of respondents were aware of the influence while 23.7% were unaware and 22.0% were uncertain. Overall, respondents believe that halal-based vinegar products are guaranteed, so this study implies that the government should enforce the use of halal logos in each product as well as state the alcohol content in the products produced through the fermentation process.